(untitled) (Academicia Globe: Inderscience Research, 2023)
The acquisition of state independence by the Republic of Uzbekistan necessitated the development of an independent foreign policy activity of the state and its integration into the system of world politics. One of the directions of this process is the development of direct and multilateral relations with the countries that form the Commonwealth of Independent States (hereinafter referred to as the CIS, the Commonwealth). This Commonwealth was established on December 21, 1991 in Alma-Ata, where 11 leaders of independent states signed a declaration on the interaction of the members of the Commonwealth. Uzbekistan supported the idea of the Commonwealth and became one of its founders. For the states of the Commonwealth, multilateral and bilateral treaty relations based on equal partnership are a natural process. This process is based not only on the territorial proximity and economic interconnectedness of the Commonwealth countries, but also on deep historical roots, cultural and spiritual ties, and the common destinies of peoples over a long historical period.